DAMPAK PENDEKATAN OPEN INNOVATION TERHADAP KINERJA INOVASI PERUSAHAAN DI INDONESIA - Siti Fadhilah (Research Center and Case Clearing House PPM School of Management, 2018)
Open innovation is an approach that involves not only internal company, but also external parties in developing and integrating new ideas optimally for the benefit of the company. This approach is more applied by companies in innovating to cope with the business world whom very competitive. However, research through this approach is still minimal and the concept has not been fully adopted in Indonesia. Therefore, the purpose of this research is to know how the influence of open innovation approach and the factors supporting the development of innovation on innovation performance in Indonesian companies. The scope of this research is Indonesian companies engaged in all industrial sectors (both manufacturing and service sectors), which conducts innovation activities for the last 3 years, from 2011 to 2013. The research method is quantitative with statistical data analysis descriptive and inferential ie regression analysis. The result of the research shows that the open innovation approach model has a significant influence on the innovation performance of the company, but only two of the three variables approach are inter-organizational collaboration and technology acquisition which has significant influence. For both factors supporting the development of innovation ie the source of information (both internal and external) and internal R D, factors that have a significant influence on innovation performance of the company only internal R D alone.